MODERN METHODS OF RESEARCH-BASED TEACHING AND LEARNING: FOREIGN EXPERIENCE - Bulvinska, Oksana (Educological discourse, 2019)
The article describes theoretical foundations of research-based teaching and learning, their role in shaping a research competence of students, their critical and creative thinking. It has been pointed out that research-based teaching and learning is one of the main trends of modern European education, enshrined in the European Higher Education Area (EHEA) strategic and analytical documents. The model of scientific researches integration in the educational process of a university is considered, which is constructed using 2 criterias: a degree of students perception of scientific problems and a degree of students involvement in a scientific research work. The experience of research-based teaching and learning, from universities of different countries (Japan, UK, Australia, New Zealand, USA, Canada) is analyzed and classified according to the methods of educating. It is noted that the most effective methods for a development of the students’ researches competence are active methods, which stimulate active mental and practical performance during an acquisition of educational material. Students participate in a process of cognition; they exchange information, analyze it, consider alternative thoughts, participate in a discussion, model situations, evaluate the actions of others and their own behavior, make thoughtful decisions, that is, collectively solve educational and scientific problems, plunging into a real atmosphere of scientific cooperation. Specific attention is paid to such active learning and educating methods as project method, case method, discussions, research method, game techniques, communication with leading scientists, specialty practical activity as well as an introduction of scientific research results into production.